2016
DOI: 10.1055/s-0036-1583758
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Long Acting Reversible Contraceptives and the Relationship between Discontinuation Rates due to Menopause and to Female and Male Sterilizations

Abstract: Introduction Women require effective contraception until they reach menopause. The long acting reversible contraceptives (LARC) and the depot-medroxyprogesterone acetate (DMPA, Depo-Provera®, Pfizer, Puurs, Belgium) are great options and can replace possible sterilizations. Purpose To assess the relationship between the use of LARCs and DMPA and terminations ascribed to menopause and sterilizations in a Brazilian clinic. Methods We reviewed the records of women between 12 and 50 years of age attending the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The authors attribute the high continuity rate of LARCs and DMPA observed in the study to the appropriate orientation regarding the high efficacy of these methods (B). 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors attribute the high continuity rate of LARCs and DMPA observed in the study to the appropriate orientation regarding the high efficacy of these methods (B). 20 …”
Section: Resultsmentioning
confidence: 99%
“…The authors attribute the high continuity rate of LARCs and DMPA observed in the study to the appropriate orientation regarding the high efficacy of these methods (B). 20 Higher continuity rates were associated to the beginning of the use of a LARC method in the postpartum period and to higher satisfaction rates (C). 21 A study with American students found higher acceptance rates of LARCs among adolescents with previous history of vaginal intercourse and younger age (C).…”
Section: Acceptance and Continuitymentioning
confidence: 99%
“…The annual number of sterilizations dropped markedly in the same period, as we can observe in this issue of RBGO. 16 In addition to a positive impact on women's health outcomes, increasing LARC uptake has also a favorable economic impact. 17 For example, it was estimated that if 10% of women aged 20-29 years in the US switched from oral contraception to LARCs, the total cost of unplanned pregnancies would be reduced by US$ 288 million per year.…”
mentioning
confidence: 99%